2011
DOI: 10.1089/jpm.2011.0032
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Medicine and Decision Science: The Critical Need for a Shared Agenda To Foster Informed Patient Choice in Serious Illness

Abstract: Assisting patients and their families in complex decision making is a foundational skill in palliative care; however, palliative care clinicians and scientists have just begun to establish an evidence base for best practice in assisting patients and families in complex decision making. Decision scientists aim to understand and clarify the concepts and techniques of shared decision making (SDM), decision support, and informed patient choice in order to ensure that patient and family perspectives shape their hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 60 publications
1
66
0
3
Order By: Relevance
“…Research focused on the quality of decisions at the end of life has been identified as a national priority in both the fields of decision science and palliative medicine 25 and represents an important next step in evaluating the POLST program. 15 The findings from this pilot study suggest that better tools and methods are needed to assess the quality of POLST decisions and POLST conversations.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Research focused on the quality of decisions at the end of life has been identified as a national priority in both the fields of decision science and palliative medicine 25 and represents an important next step in evaluating the POLST program. 15 The findings from this pilot study suggest that better tools and methods are needed to assess the quality of POLST decisions and POLST conversations.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Initially, 79% of residents and 50% of surrogates expressed preferences that appeared discrepant with existing POLST orders [v 2 (1, n = 28) = 2.5, p = 0.24]. Participant explanations for the apparent discrepancies included a lack of knowledge, a lack of clarity concerning preferences, initial confusion about what was being discussed, and a lack of interest in the decisions.…”
Section: Characteristics Of the Polst Conversationmentioning
confidence: 99%
“…As a result, the best choice is heavily dependent on patient preferences rather than clinical considerations. 2,3 The generally accepted best practice is to discuss and document end-of-life treatment preferences well in advance of the need for treatment due to concerns that patients will be unable to participate in decision making about critical decisions when the time comes. This can result in a gap of weeks, months, or even years between the discussion and when an advance care plan is acted upon.…”
mentioning
confidence: 99%
“…These include, but are not limited to, decisions Align treatment plans and quality metrics to optimize patient-important goals and preferences to maximize patient quality of life Encourage regulatory and practice changes to allow for greater flexibility in the timing and prescription of dialysis and the development of strong positive treatment alternatives to dialysis Promote regulatory changes for greater integration of hospice and palliative care into other aspects of the care of patients with advanced kidney disease as needed to support patient goals and preferences Increase palliative care training, both in nephrology fellowship programs and continuing medical education about dialysis initiation, continuation, and discontinuation and may also pertain to related interventions (e.g., treatment modality for advanced kidney disease, choice and timing of vascular access placement, referral for kidney transplant) as well as broader efforts to maintain health (e.g., renoprotective and cardioprotective interventions). The emerging field of decision science and associated tools (e.g., decision aids) may be extremely helpful in supporting many of these decisions (56).…”
Section: The Csckp's Vision For the Medicare Esrd Programmentioning
confidence: 99%